LINE Insertion Polymorphisms are Abundant but at Low Frequencies across Populations of Anolis carolinensis - Ruggiero, Robert P.; Bourgeois, Yann; Boissinot, Stéphane (Frontiers in Genetics, 2017)
Vertebrate genomes differ considerably in size and structure. Among the features that show the most variation is the abundance of Long Interspersed Nuclear Elements (LINEs). Mammalian genomes contain 100,000s LINEs that belong to a single clade, L1, and in most species a single family is usually active at a time. In contrast, non-mammalian vertebrates (fish, amphibians and reptiles) contain multiple active families, belonging to several clades, but each of them is represented by a small number of recently inserted copies. It is unclear why vertebrate genomes harbor such drastic differences in LINE composition. To address this issue, we conducted whole genome resequencing to investigate the population genomics of LINEs across 13 genomes of the lizard Anolis carolinensis sampled from two geographically and genetically distinct populations in the Eastern Florida and the Gulf Atlantic regions of the United States. We used the Mobile Element Locator Tool to identify and genotype polymorphic insertions from five major clades of LINEs (CR1, L1, L2, RTE and R4) and the 41 subfamilies that constitute them. Across these groups we found large variation in the frequency of polymorphic insertions and the observed length distributions of these insertions, suggesting these groups vary in their activity and how frequently they successfully generate full-length, potential active copies. Though we found an abundance of polymorphic insertions (over 45,000) most of these were observed at low frequencies and typically appeared on a single chromosome. Site frequency spectra for most LINEs showed a significant shift towards low frequency alleles compared to the spectra observed for total genomic single nucleotide polymorphisms. Using Tajima’s D, FST and the mean number of pairwise differences in LINE insertion polymorphisms, we found evidence that negative selection is acting on LINE families in a length-dependent manner, its effects being stronger in the larger Eastern Florida population. Our results suggest that a large effective population size and negative selection limit the expansion of polymorphic LINE insertions across these populations and that the probability of LINE polymorphisms reaching fixation is extremely low.